Farmer’s Satisfaction in Joining Organic Rice Partnership: An Empirical Case in Ngawi, East Java, Indonesia - Tiffany Rahma Abdillah; Ainun Faidah; Yogy Rasihen; Suwali Suwali (Program Studi Agribisnis, 2026)
Rice is strategic commodity which has developed in organic and conventional farming systems. People nowadays are aware of the importance of healthy food. This can increase demand for organic rice. However, most of rice farmers still apply conventional farming with some reasons. Ngawi Organic Center Community is a partner for organic rice farmers in Ngawi, East Java since 2010. Several obstacles emerged in the implementation of the partnership. This can caused farmers don’t want to continue the partnership and finally this can affect supply of organic rice and Ngawi Organic Center Community unable to meet market demand. This study aimed to describe the partnership pattern and analyze the level of satisfaction of farmers during the partnership. Data are processed by descriptive analysis and quantitatively by IPA and CSI approach. As a conclusion, partnership pattern is Agribusiness Operational Cooperation. The main point for improvement is the organic rice seed quality, timeline payment of harvest and an ease of transportation during harvest. The CSI value is 86,20 percent so that it can be said that the organic rice farmers are very satisfied. In the future, a complete written contract agreement will be required that includes sanctions for violators.